LINGUOCULTURAL PECULIARITIES OF ENGLISH ANECDOTES. - Shomurodova Sabina Shuxratovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article investigates the linguocultural features of English anecdotes, focusing on how humor reflects cultural values, communicative norms, and national identity. Using discourse and pragmatic analysis, it reveals how stereotypes, irony, and semantic incongruity serve as key humor mechanisms. The findings highlight the cultural specificity of English humor.